U źródeł chaosu. Relacje słowa i obrazu w Czarnych kartach grupy Oneiron - Szweda, Joanna (Przestrzenie Teorii, 2022)
The article presents the first extended discussion of the structure of Oneiron’s Black Cards – the neoavantgarde project connecting image and word. Using literary instruments, the author attempts to read this work on three basic levels: the perception of the series, the analysis of the space of every single card, and an attempt to decipher the autonomous “micro-works” falling into the card area. Multilayerism refers to the original premise of the creators. Thanks to their collective and aleatory work, Black Cards were meant to reflect the game of the subconscious. This reading of the Cards on three levels is aimed at identifying the sources of inspiration of the artists participating in the workand determining the role of words and literature in this multifaceted intention.